Tongkonan as a Digital Community Literature Center: Empowerment of the Youth Generation of Lembang Lempo Poton, North Toraja - Lisa Kurniasari Wibisono (Budapest International Research and Critics University, 2022)
Children from the alpha generation were born among the widespread use of technology along with the entry of the industrial revolution 4.0. The interaction that occurs intensively between the alpha generation and various technological equipment, makes this generation naturally have a much higher technology acceptance ability than their parents from the previous generation. Therefore, encouraging the creation of a digitally minded young generation was chosen as one of the programs in the UKI Toraja Student Community Service Program Class XXXVIII which was held in Lembang Lempo Poton, Rindingallo District, North Toraja Regency, South Sulawesi Province. In the program, the use of Tongkonan to be directed as a digital literacy center for indigenous peoples is also expected to be useful in creating a digital-minded community of children. The development of Tongkonan towards a digital literacy center for the local indigenous community is not an easy thing, because it requires not only the participation of the campus community but also a large role from the local government, especially the North Toraja Regency government of Rindingalo.